(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2013)
Since World War II a special kind of counselling has been developed in the Netherlands, called ’humanist counselling’. The word ’humanist’ here refers to humanism, a secular life stance. Humanist counselling belongs to the same professional category of spiritual counselling as pastoral counselling, a category that differs from psychotherapy (Mooren, 1989). Humanist counsellors work in hospitals, asylums, homes for the elderly, the armed forces and prisons, alongside Roman Catholic and Protestant pastoral counsellors, Jewish rabbis, Islamic imams and Hindu pundits. This paper describes the way in which humanist counsellors working in correctional institutions might deal with the moral dimension in the life stories of the inmates as well as in their attitudes towards other human beings. Using the counselling model of van Deurzen, the focus of the existential communication is on moral experience rather than on moral reasoning.